The Implementation of Regional Regulation Number 5 of 2021 Concerning Prevention of Child Marriage to Improve the Human Development Index in West Nusa Tenggara - Karyati, Sri; Ulum, Hafizatul; Susilawati, Ika Yuliana (Faculty of Law, Universitas Pekalongan, 2024)
Child marriage is a problem that has a negative impact on social and economic development, especially in the West Southeast Nusa Province. The high child marriage rate in West Nusa Southeast contributes to the low Human Development Index (HDI) in the region. To address this problem, the local government issued Regional Regulation (Perda) No. 5 of 2021 on Prevention of Child Marriages. The study aims to evaluate the implementation of the Perda and assess its impact on the increase in the Human Development Index in West Southeast Nusa. The method used in this research is a normative supported by empirical research. Based on the implementation of District Regulation No. 5 of 2021 on the prevention of child marriage in West Nusa Tenggara, so far it has not been implemented optimally both politically and institutionally. As a result, the objective of District Regulation No. 5 for 2021 has not been achieved optimally. Therefore, the political will of the West Southeast Nusa region's government needs to be committed to both legal policy, education policy, health policy and budgetary policy in favour of child marriage prevention.